Asthma Medication Use in Congenital Diaphragmatic Hernia Survivors: A Retrospective Population Level Data Analysis - Levesque, Matthew; Lum Min, Suyin A.; Morris, Melanie I.; Shawyer, Anna C.; Keijzer, Richard (European Journal of Pediatric Surgery, 2020)
Introduction The purpose of this study was to determine if congenital diaphragmatic hernia (CDH) survivors had worse long-term respiratory outcomes compared with age-matched controls, as measured by inhaled bronchodilator use, inhaled steroid use, and asthma-related physician visits.Materials and Methods We performed a retrospective case-control study of infants with isolated CDH from 1991 to 2013. The primary outcome measures were inhaled bronchodilator prescriptions, inhaled steroid prescriptions, and asthma-related physician visits between 0 and 5 years of age and between 5 and 10 years of age. Subgroup analysis compared the same outcomes for CDH patients grouped by: birth weight, gestational age, side of defect, defect size, liver herniation, hernia sac, and pulmonary hypertension.Results Fifty-six patients with CDH and 753 age-matched controls met the inclusion criteria for the 0 to 5 years of age analysis. Between 0 and 5 years of age, more CDH survivors were prescribed an inhaled bronchodilator (odds ratio [OR] = 2.47[1.38–4.48], p = 0.001) and inhaled steroid (OR = 2.03[1.07–3.74], p = 0.03), and had an asthma-related physician visit (OR = 1.92[1.00–3.56], p = 0.04). Thirty-eight cases and 491 controls met the inclusion criteria for the 5 to 10 years of age analysis. Between 5 and 10 years of age, CDH survivors were not more likely to be prescribed inhaled bronchodilators, inhaled steroids, or have an asthma-related physician visit. Among the CDH patients, we did not find a clinical characteristic associated with increased inhaled bronchodilator or steroid prescriptions at any age.Conclusion A history of CDH is associated with higher rates of inhaled bronchodilator prescriptions, inhaled steroid prescriptions, and asthma-related physician visits from 0 to 5 years of age compared with age-matched controls. However, this difference resolves by 5 to 10 years of age.
Keywords: congenital diaphragmatic hernia; long-term outcomes; respiratory outcomes